Behind the Seams: Unveiling the Hidden Threads of Cambodia and Vietnam’s Garment Industry - Mababangloob, Maxine Denise Q.; Hizon, Chloe Heart B.; Perez, Renee Patricia R.; Dizon, Avielle Elize (WIMAYA, 2025)
This article examines how labor exploitation among garment workers in Cambodia and Vietnam arises from the interaction of legal governance, economic development strategies, and cultural belief systems. Despite contrasting political regimes, Cambodia’s fragmented pluralism and Vietnam’s centralized authoritarianism, both countries produce similar exploitative outcomes: weak enforcement of labor protections, constrained worker representation, and persistent precarity. Using a most different systems design supplemented by an assemblage approach, the study analyzes how export-oriented growth and integration into global supply chains exert downward pressure on wages and working conditions. It also explores how religious and ethical worldviews, such as karmic endurance in Cambodia’s Theravāda Buddhism and moral restraint shaped by Mahāyāna Buddhism and Confucianism in Vietnam, inform how workers interpret, endure, and sometimes symbolically resist their conditions. These belief systems function as informal mechanisms of governance, sustaining compliance where institutional safeguards fail. By deploying assemblage theory in a comparative analysis of Cambodia and Vietnam, this article challenges reductionist accounts of labor exploitation by presenting how it emerges through the contingent alignment of fragmented legal authority, transnational economic imperatives, and internalized moral frameworks.